Speech Genre of Consolation in the Context of Foreign Language Learning at a Medical University - Hrytsenko, O. V.; Solianenko, O. L.; Гриценко, Ольга Вікторівна; Соляненко, Олена Леонідівна (My University, 2024)
Abstract—Empathy, which involves supporting the client, is a mandatory component of doctor-client communication. Sticking to the tactics of consolation in communication allows achieving greater effectiveness of the clinical activity of a medical worker. Since medical discourse as a sample of institutional discourse is characterized by a certain constant pattern, it has been proven that in the context of learning a foreign language it is appropriate to use a genre approach. The involvement of the genre approach in linguistic didactics is also explained by the dependence of the number of speech genres mastered by a foreigner and his level of formation of the secondary language personality. It is proved that consolation is a speech genre. The choice of film discourse for the study is justified by the specificity of the genre and the fact that it is a sample of authentic texts, the effectiveness of the auditory and visual channels of information perception. The "signals" of the use of the consolation genre, vocabulary and grammatical features are described. The verbal means of the main tactics within the secondary genre of consolation are listed Ukrainian language according to the genre approach are proposed.
Keywords: speech genre; consolation; genre approach to learning